Evaluation of an Arab American AD care intervention program in the United States. (1st February 2022) - Ajrouch, Kristine J; Janevic, Mary; Alhamood, Ammar J; Antonucci, Toni C
Abstract: Background: This initiative is part of a program of research designed to maximize the health and quality of life within the large Arab‐American community in Michigan through cultural/linguistic adaptations of the Alzheimer's Association's Living with Alzheimer's education and support strategies program. Further, we aim to break new ground in terms of explicitly focusing on family systems as part of a caregiver support intervention. Methods: 10 families (two individuals from each, for a total of 20 individuals) signed up to attend the program. The program was offered twice virtually due to COVID‐19, delivered by bi‐lingual Arab American trainers. All participants were sent a link to an evaluation survey after completing the program (1=strongly disagree; 5=strongly agree) on: the usefulness of the program, the tip sheet, the language of delivery, and Alzheimer's Association resources. Descriptive analysis was conducted to ascertain rating frequency. Results: Session 1 was delivered in English. Results showed that overall, all respondents agreed that the program was useful in that they learned something new and improved their caregiving skills. Half reported they neither agree/disagree about whether the program met their expectations with. Less than half reported they planned to use the Alzheimer's Association resources available to them. Session 2 was delivered in Arabic. Results showed that overall, all respondents strongly agreed that the program was useful in that they learned something new and improved their caregiving skills. More than half strongly agreed the program met their expectations. More than half reported they planned to use the Alzheimer's Association resources available to them. When asked "What would you change about this program" replies from both sessions asked to receive more strategies on how to deal with family members with Alzheimer's. They also reported liking the Q&A time because that alleviated their feelings of the stigmatization of Alzheimer's. As one said, "I felt at ease talking and sharing my experience with people who know what am I talking about." Conclusion: Identifying successful and challenging elements of the adapted intervention will enable the creation of a program tool kit, which will set the stage for full‐scale broader implementation in underserved diverse populations.